Advanced Composite Technologies for High-Performance Sports Equipment: Materials, Manufacturing, and Sustainability Perspectives - Temesgen, Alhayat Getu; Koc, Umit; Kaufmann, Jorg; Cebulla, Holger; Aydogmus, Ercan; Arslanoglu, Hasan (Wiley, 2026)
Advanced composite materials have become the leading material platform for high-performance sports equipment, enabling superior strength-to-weight performance, stiffness tailoring, and enhanced functional integration compared with conventional materials. This review summarizes state-of-the-art developments across multiple sporting disciplines, focusing on recent innovations in fiber reinforcements, matrix chemistries, hybrid architectures, and advanced manufacturing routes. Key material advances include nano-enhanced carbon fibers, spread-tow fabric concepts that improve laminate uniformity and surface quality, and the growing use of natural-fiber composites to support sustainability goals while maintaining adequate mechanical efficiency for targeted components. On the manufacturing side, automated fiber placement, additive manufacturing of continuous-fiber composites, and resin transfer molding (RTM) variants are examined as enabling technologies for precision lay-up control, geometric complexity, repeatability, and scalable production. Application-driven progress in cycling, racket sports, golf, water sports, and winter sports is discussed through the perspective of performance enhancement, weight minimization, durability, and regulatory constraints. Emerging research directions-bio-inspired structural concepts, smart composites with embedded sensing, and circular-economy strategies-are critically assessed in relation to environmental impact and end-of-life challenges. The review also highlights the accelerating role of computational design and optimization tools, including topology optimization, multiscale modeling, and machine learning, in shortening development cycles and guiding material/process selection. Performance validation is addressed by integrating mechanical characterization, sport-specific testing protocols, and nondestructive evaluation approaches to ensure reliability and safety. This synthesis outlines current capabilities, identifies key research gaps, and provides future recommendations toward sustainable, adaptive, and biomimetic composite systems for next-generation sports equipment.
Keywords: Advanced Composite Manufacturing; Carbon-Fiber-Reinforced Polymers; High-Performance Sports Composites; Sustainable And Recyclable Composites